The Effect of Antioxidant Compounds on Glycemic Index (GI) and Glycemic Response (GR) - Yuli Indarti, (Journal of Health Science Community, 2022)
Blood sugar levels are influenced by the glycemic index (GI) and glycemic response (GR) of a person's food intake. The GI and GR levels of a substance are influenced by several things. A good understanding of a food ingredient is needed to maintain a balanced diet. Antioxidant levels are also thought to affect the GI and GR. The search for articles in the literature review was carried out through Scientdirect, PubMed and Google Search from 2010–2018. Based on the results of the study showed that antioxidants were associated with GI and GI parameters of foods containing carbohydrates. The effect of these antioxidant compounds on the glycemic index and glycemic response is through glucose metabolism and carbohydrate digestibility. Thus, supplementation or accompanying foods containing these compounds have the potential to control blood glucose. so that indirectly these foods can prevent non-communicable diseases, especially Diabetes Mellitus.